The institutional dimensions of environmental change : fit, interplay, and scale - Young, Oran R. (Global environmental accords., 2002)
Researchers studying the role institutions play in causing and confronting environmental change use a variety of concepts and methods that make it difficult to compare their findings. Seeking to remedy this problem, Oran Young takes the analytic themes identified in the Institutional Dimensions of Global Environmental Change (IDGEC) Science Plan as cutting-edge research concerns and develops them into a common structure for conducting research. He illustrates his arguments with examples of environmental change ranging in scale from the depletion of local fish stocks to the disruption of Earth's climate system. Young not only explores theoretical concerns such as the relative merits of collective-action and social-practice models of institutions but also addresses the IDGEC-identified problems of institutional fit, interplay, and scale. He shows how institutions interact both with one another and with the biophysical environment and assesses the extent to which we can apply lessons drawn from the study of local institutions to the study of global institutions and vice versa. He examines how research on institutions can help us to solve global problems of environmental governance. Substantive topics discussed include the institutional dimensions of carbon management, the performance of exclusive economic zones, and the political economy of boreal and tropical forests.